Pendampingan Pencantuman Informasi Nilai Gizi pada Packaging Madu Trigona Peternak Lebah dalam Meningkatkan Penjualan - Yunita, Lina; Sukanty, Ni Made Wiasty; Dewi, Novianty Tysmala; Ariani, Farida (LPPM Universitas Bumigora, 2024)
Bengkaung Village is a village in the Batulayar District, West Lombok Regency, NTB Province. The great potential of trigona honey bee cultivation in Bengkaung Village can be further developed and supported by the abundant availability of bee feed. Cultivation of Trigona honey bees produces genuine honey which is efficacious for health. Trigona honey bee cultivation is one of the entrepreneurs that can be introduced to the wider community, so that it can increase income. Bengkaung Village is one of the villages that produces honey with good quality, it's just that there is a problem that does not include nutritional value information on the packaging. This is because the packaging design and the inclusion of labeling nutriton fact have an influence on potential buyers to purchase the product. This activity aims to increase knowledge about the function of food labels and how to include information on food labels in accordance with laws and regulations, so partners are expected to be able to understand what information must be included at a minimum and what information is prohibited from being included on food labels so that partners make designs. Food labels that are not only attractive but also in accordance with statutory regulations. This is a solution related to solving problems in Bengkaung Village, especially for Trigona Beekeepers. With the dissemination of packaging design by including information on nutritional value for Trigona honey packaging products, beekeepers get an increase in sales